Sustained Decrease of Early-Phase Insulin Secretion in Japanese Women with Gestational Diabetes Mellitus Who Developed Impaired Glucose Tolerance and Impaired Fasting Glucose Postpartum - Katayama, Hiroko (Jpn Clin Med, 2015)
OBJECTIVE: The aim of this study was to compare glucose intolerance in the antenatal and the postpartum periods using a 75-g oral glucose tolerance test (OGTT) in the Japanese women with gestational diabetes mellitus (GDM) using a retrospective design. PATIENTS AND METHODS: Data were obtained from 85 Japanese women with GDM who delivered from April 2011 through April 2015 and who underwent an OGTT 6–14 weeks postpartum. The women were divided into two groups based on the results of the postpartum OGTT: one group with normal glucose tolerance (NGT) and the other with impaired glucose tolerance (IGT) as well as impaired fasting glucose (IFG). We analyzed the associations between postpartum IGT–IFG and various factors. RESULTS: Antenatally, a significant difference was observed between the groups only in the 1-hour plasma glucose level of the 75-g OGTT. Postpartum results of plasma glucose level were significantly higher at 0.5, 1, and 2 hours in the IGT–IFG group than those in the NGT group. Moreover, a significant decrease in the levels of 0.5-hour immunoreactive insulin and insulinogenic index was observed in the IGT–IFG group compared to those in the NGT group. Homeostasis model assessment-insulin resistance and homeostasis model assessment β-cell function of both groups were found to significantly decrease in the postpartum period; however, there was no significant change in the insulinogenic index of either group. CONCLUSIONS: Our study clearly showed that the postpartum IGT and IFG levels of Japanese women with GDM are affected by impaired early-phase insulin secretion; however, insulin resistance promptly improves.